A Review paper on Detection of Moving Object in Dynamic Background - Vayadande, Kuldeep B; Karande, Nikhil D; Yadav, Surendra (International Journal of Computer Sciences and Engineering, 2025)
Recent work in computer vision and image processing has increasingly focused on developing systems for monitoring humans and understanding their look, activities, and behaviour providing advanced interfaces for interacting with human beings, and developing sensible models of humans for various purposes. Moving target detection is a fundamental problem in computer vision, due to the features of moving target, such as strong speed degeneration, uncertain route, dynamic background, it becomes hard to detect moving object. The study on moving object in literature do not guarantee high precision and recall, so there is chance of improvement in detecting moving object in dynamic background with greater precision and recall.